Book Reviews (Rev. Anal. Numér. Théor. Approx., 2002)
Book reviews for:Victor Y. Pan, Structured Matrices and Polynomials: Unified Superfast Algorithms, Birkhauser, Boston, 2001, ISBN 0-8176-4240-4 and 3-7643-4240-4, XXV+278 pp. Reviewed by E. Catinas.Titus Petrila and Damian Trif, Numerical and Computational Methods in Fluid Dynamics, Editura Digital Data, Cluj-Napoca, 2002, ISBN 973-82011-2-8, 506 pp. (in Romanian). Reviewed by A. Georgescu.Gilbert, W. Stewart, Afternotes on Numerical Analysis, SIAM, Philadelphia, 1996, ISBN 0-89871-362-5, X+200 pp. Reviewed by M. Craciun.G. Kwanty and G. L. Blankenship, Nonlinear  Control  and  Analytical  Mechanics.  A Computational Approach, Birkhauser, 2000, XV+317 pp., ISBN 0-8176-4147-5. Reviewed by C. I. Gheorghiu.Michael L. Overton, Numerical Computing with IEEE Floating Point Arithmetic, SIAM, Philadelphia, 2001, ISBN 0-89871-482-6, XI+104 pp. Reviewed by E. Catinas.Gilbert, W. Stewart, Afternotes Goes to Graduate School:  Lectures on Advanced Numerical Analysis, SIAM, Philadelphia, 1998, ISBN 0-89871-404-4, XII+245 pp. Reviewed by E. Catinas.Gilbert, W. Stewart, Matrix Algorithms. Volume I: Basic Decompositions, SIAM, Philadelphia, 1998, ISBN 0-89871-414-1, XIX+458 pp. Reviewed by E. Catinas.